Analisis Problem Based Learning dan Discovery Learning menggunakan Macromedia Flash pada materi Termokimia - Freddy Tua Musa Panggabean; Muhammad Fadli Harahap (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
This study aims: (1) to find out wheter the average value of student learning outcomes taught by PBL and DL models is greater than the KKM value (2) to find out whether there is class interaction and motivation on the value of student learning outcomes. This research is type of One-Group pretest-posttest Design research. The analysis technique used is: (1) One sample t-test; (2) Two Way Anava. From the analysis of the learning outcomes data obtained (1) differences in student learning outcomes (80.47  8.3336) taught by applying PBL models using macromedia flash and student learning outcomes (78.269  9.994) are taught by applying the DL model using macromedia flash where a t test of 1.684 is obtained; (2) There a Fhit price of 6.235 > Ftable 4.00 and a sig value of 0.015 < 0.05 meant that the factor A was real; inter-row results (B) have a Fhit price of 0.025 < Ftable 4.00 and a sig value of 0.975 > 0.05 means that the factor B is not real; interaction results (AB) has a Fhit price of 3.860 > Ftable 3.45 and a sig value of 0.027 < 0.05 means that the factor AB is real.